Influence of orthodontic force on immediately loaded implants (Research, Society and Development, 2021)
This study aimed to evaluate the influence of orthodontic force on dental implants subjected to immediate loading in adult’s human patients. For this patients with absence of mandibular posterior teeth undergoing orthodontic treatment, whose planning requires skeletal anchorage, were selected and submitted to implant installation surgery with a Morse Cone prosthetic connection and a torque of 45 N.cm. After the molding, confection and installation of the provisional prostheses in infraocclusion, Edgewise/Ricketts lower double-tube orthodontic fittings were bonded, and the mechanics of the accompanying arches for the molar verticalization were initiated, supported by the implant force ranging from 50 to 150 g, up to 6 months. Marginal bone loss and Resonance Frequency Analysis (RFA) were performed at T0 - immediately after provisional installation and T1 – 180 days after implantation. The results showed a total of 9 patients were initially selected, totaling 10 implant surgeries. However, only 5 implants presented primary stability greater than 45 N.cm. Marginal bone loss analysis showed an average of 1.21 ± 1.66 mm of bone losses, no statistically significant differences (P = 0.690) between the mesial (1.09 ± 1.6 mm) and distal (1.34 ± 1.9 mm) regions was observed. The RFA results showed a significant difference (P=0.008) in the ISQ values presented between the T0 (67.3 ± 11.7) and T1 (76.8 ± 4.95). The conclusion showed the orthodontic force does not interfere with the stability of immediate loading implants. Further studies with larger sampling and extended evaluation times are necessary to attain more consistent results.